Bioenergy and agriculture: Promises and challenges: Bioenergy in developing countries: Experiences and prospects - Kammen, Daniel M. (International Food Policy Research Institute, 2006)
Biomass energy programs offer a wide range of potential benefits for developing countries. Already traditional biomass products like firewood, charcoal, manure, and crop residues provide the main source of household energy use for some 2–3 billion people in the developing world, and this demand is likely to grow in the years ahead. But new technologies for commercial energy production from biomass are emerging that could lead to dramatic new opportunities for agriculture and the rural sector, as well as help developing countries reduce their dependence on expensive oil imports. Both the traditional and the new options for biomass energy pose challenges that will require technology and policy solutions to ensure efficient, healthy, and environmentally sustainable outcomes.